Effect of Rearing Density on Growth and Survival Rate of Balashark (Balantiocheilus melanopterus Blkr.) Fry at Recirculation Culture System - I. Effendi; T.D. Ratih; T. Kadarini (Jurnal Akuakultur Indonesia)
Population of balashark (Balantiocheilus melanopterus, Blkr.) in nature has been decreased.  Therefore, domestication is needed to recover the stock and meet the market demand.  This study was conducted to determine rearing density producing the best survival and growth rate of fish.  Fry of balashark in length of 1.5 cm and body weight of 0.2 g were reared at density of 1, 2, 3 and 4 fish/l in recirculation aquarium 50×50×40 cm3 system.  During experiment, fish were fed on Tubifex two times daily at 15% body weight or 0.168 g/fish.  Sampling of fish length and body weight was done every two weeks by 10% of population.   Data were analyzed using ANOVA and polynomial orthogonal test.  The results indicated that daily growth rate by weight (Y1) of fish decreased by increasing the rearing density (X).  Response of daily growth rate related to rearing density was negatively linear as Y1= 7.3563 - 0.253X.  Daily growth rate by length was also decreased by increasing the rearing density.  Their response was also negatively linear as Y2 = 0.7411 - 0.0358X. Food efficiency of was decreased by increasing the rearing density at 0.69, 0.61, 0.53 and 0.36%, respectively.  Survival rate of fish in each treatment was relatively similar, ranged from 95.0 to 98.5%.   Thus, best growth and survival rate were obtained by rearing fish at density of 1 fish/l.